2021
DOI: 10.3390/vaccines9101120
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Proof of SARS-CoV-2 Infections in Indigenous Wiwa Communities in North-Eastern Colombia—A Cross-Sectional Assessment Providing Preliminary Surveillance Data

Abstract: To provide initial data on local SARS-CoV-2 epidemiology and spread in indigenous communities in north-eastern Colombia, respiratory swabs and serum samples from volunteers of indigenous communities were examined in March and April 2021. Samples from non-indigenous Colombians from the same villages were included as well. While previous exposure to SARS-CoV-2 was assessed by analysing serum samples for IgG and IgM with a rapid antibody point-of-care-test (POCT), screening for active infections was carried out w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…After excluding studies which contained duplicate patient data, 77 studies comprising over 200,000,000 confirmed COVID-19 cases were included. 4 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , ...…”
Section: Resultsmentioning
confidence: 99%
“…After excluding studies which contained duplicate patient data, 77 studies comprising over 200,000,000 confirmed COVID-19 cases were included. 4 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Finally, potential bias due to different assessment periods cannot be excluded, and more sampling would have been desirable as well, but was, unfortunately, unfeasible due to resource limitations of the study under the local conditions given. The study setting was affected by the COVID-19 pandemic in 2020, as described in more detail elsewhere [89,90], a situation which might have interfered with the registration of side effects.…”
Section: Discussionmentioning
confidence: 99%
“…The present study was implemented to analyze immunity towards SARS-CoV-2 and the endemic human coronaviruses in children living in urban Bogotá and from the indigenous Wiwa community. The samples analyzed in this study were collected as part of two previous studies conducted in Colombia in March and April 2021 22 , 23 . A detailed overview on the sample selection strategy from the two initial studies is provided in Supplementary Figs.…”
Section: Methodsmentioning
confidence: 99%
“…Serum samples from individuals of the Wiwa community living in the Sierra Nevada de Santa Martha in the North-East of Colombia were collected between 28 March 2021 and 26 April 2021 as part of an independent observational study 23 . As part of this initial study, sera and nasal swabs were sampled to assess the extent of SARS-CoV-2 dissemination by using Point-of-care (POC) SARS-CoV-2 antibody-, POC antigen-, and polymerase chain reaction (PCR)-based molecular testing 23 . All study participants received their SARS-CoV-2 molecular and serological test result as part of the previous study.…”
Section: Methodsmentioning
confidence: 99%